MODEL PREDIKSI FINANCIAL DISTRESS DENGAN BINARY LOGIT ( STUDI KASUS EMITEN JAKARTA ISLAMIC INDEX) - Azwar Azwar (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2015)
The purpose of this research were to analyze : (i) Financial ratios choosen as predictor for financial distress prediction ; (ii) accuration rate of prediction model that formed from analysis. The data used was from resume of financial report of companies at Indonesia Stock Exchange periode of 2012-2013. This research used 23 companies of JII as samples with purposive sampling method. This research used binary logit regression analysis. The empirical result shown that the financial ratios such as Current ratio (CR), Operating profit margin (OPM) Return on Asset (ROA), Return on Equity (ROE), and yield (YLD) can be used for comparing and classifying companies to distress and non-distress group. The financial ratios such as ROA and ROE significantly can be used predition model with accuration rate of 90.9% that model also can be as early warning signal. For regulators such BEI and Otaritas Jasa Keuangan can Use it as tool for evaluating, reviewing and controlling of companies.